1997
DOI: 10.1038/sj.onc.1200979
|View full text |Cite
|
Sign up to set email alerts
|

p53 induced by ionizing radiation mediates DNA end-jointing activity, but not apoptosis of thryroid cells

Abstract: To understand the eects of ionizing radiation on thyroid cells, we investigated the role of p53 in mediating apoptosis and in DNA repair following in vivo and in vitro irradiation of thyroid cells. In vitro exposure of human thyroid cells to ionizing radiation of up to 5 ± 8 Gy failed to induce apoptosis in primary cells. The same results were obtained when the thyroid gland was irradiated in the intact rat. To explore the mechanism of failure of the wild-type p53 in inducing apoptosis in thyroid cells, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 39 publications
8
40
1
1
Order By: Relevance
“…Note that p53 plays an important role in DNA repair (17). However, the effect of p53 on NHEJ is complicated: a stimulatory effect was observed (21,22), whereas an inhibitory effect was also reported (23,24). To reconcile these findings, it was speculated that p53 may inhibit error-prone repair but promote error-free repair (17).…”
mentioning
confidence: 77%
“…Note that p53 plays an important role in DNA repair (17). However, the effect of p53 on NHEJ is complicated: a stimulatory effect was observed (21,22), whereas an inhibitory effect was also reported (23,24). To reconcile these findings, it was speculated that p53 may inhibit error-prone repair but promote error-free repair (17).…”
mentioning
confidence: 77%
“…p53 certainly plays a role in DNA repair, but its regulatory role in non-homologous end joining is complicated and controversial (32). Some studies revealed that p53 can promote the rejoining of DNA with lesions (33,34), whereas inhibitory effects of p53 on non-homologous end joining were also reported (35,36). For simplicity, we did not consider the effect of p53 on DNA repair.…”
Section: Methodsmentioning
confidence: 99%
“…The relation between P53 and NHEJ is even less clear and somewhat contradictory (Bill et al, 1997;Yang et al, 1997;DiBiase et al, 1999;Tang et al, 1999), possibly because of the use of different cell types and assays in different studies. A recent report using an ISceI endonuclease-based cell system in human leukemic and lymphoblastoid cells demonstrated that expression of wild-type P53 in P53 null cells inhibits HRR as well as microhomology-directed NHEJ.…”
Section: Role Of P53 and Other Tumor Suppressors In Dsb Repairmentioning
confidence: 99%